Parotid gland tumors: clinical experience at tertiary care center - Sharma, Pritosh; Makwana, Abhijit Vasantkumar; Bishnoi, Rini; Vyas, Shifa; Goyal, Vinod Prakash (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The objective of this study is to evaluate the diagnostic accuracy of FNAC in parotid gland lesions and it’s correlation with HPE, for better management of patient. Methods: A total of 46 FNAC were done of parotid gland lesion in Pathology department of GMCH from 2016 to 2018. Out of 46 patients of parotid gland lesions 44 were surgically resected by ENT Dept GMCH and formalin fixed specimen were sent to Pathology department and slides were prepared. The cytology and HPE stained slides were studied and correlated clinically. Results: The cytology features of 44 cases are correlated with HPE. In cytology study: pleomorphic adenoma in 31, benign cystic lesion in 07, basal cell adenoma in 01, mucoepidermoid carcinoma in 04 and adenocystic carcinoma in 01. In HPE study: pleomorphic adenoma in 28, benign cystic lesion in 04, basal cell adenoma in 02 and warthin’s tumor in 02, adenocystic carcinoma in 02, mucoepidermoid carcinoma in 03, acinic cell carcinoma in 01, carcinoma of EX pleomorphic adenoma in 01 and cystadeno carcinoma in 02. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy are respectively 55.55%, 100%, 100%, 89.74% and 90.90%. Conclusions: FNAC of the parotid gland is safe and reliable technique in the primary diagnosis of salivary gland lesion. Although, sensitivity of this test has some limitation and to differentiate specific malignant lesion. This study has shown that FNAC has low sensitivity, high specificity, diagnostic accuracy, simple and cost effective for the patients of parotid gland lesion.